[70] Proximal corpora cavernosum approach for management of some penile prosthesis cylinder complications - Abdalla Alhammadi (Taylor & Francis Group, 2018)
Objective: To describe a new proximal corpora cavernosum approach for the management of some penile prosthesis cylinder complications. Penile prosthetic cylinder complications identified postoperatively are traditionally managed by approaching the corpora through the prior penoscrotal incision, risking contamination of the pump’s biofilm and giving poor exposure of the proximal cruras. This new approach addresses postoperative penile prosthesis cylinder abnormalities when they are located at the crura of a corpus cavernosum. This technique avoids any additional dissection of the previous wound, making the second surgical procedure easier and safer for the underlying implant. It also allows an optimal exposure for the required adjustment of the implant. Methods: The first step of procedure is identification of the affected part of the penis and identification of the type of penile implant anomaly. A 2-cm longitudinal skin incision is carried over the affected crura. A longitudinal incision of the tunica albuginea is done, allowing direct access to proximal part of the affected prosthesis cylinder. The prosthesis’ cylinder is then delivered through this incision allowing management of the problem under direct vision. Results: Our approach is safe, effective and can ensure that the existing penile prosthesis cylinder problem can be managed without the need to approach it through the traditional approach, which in our opinion may add difficulty to the surgery because of the adhesions from the previous intervention. In addition, using the scrotal approach may add a threat to the implant’s pump and tubing by either iatrogenic injury or possible violation of the surrounding biofilm. Conclusion: Our suggested approach is safe, simple and effective in managing some penile prosthetic cylinder complications that require access to the proximal crura and can be used for both inflatable and semi-rigid (malleable) penile prostheses.